DYNAMIC - CLIMATOLOGICAL ANALYSIS OF SIGNIFICANT LOW LEVEL CLOUDS AT BRATISLAVA - Krollová, Sandra (Doprava a spoje, 2007)
The object of the research is processing of statistical analysis of occurrence of significant low level clouds at Bratislava airport. Using the calculation of various statistical characteristics and by the applying of the dynamic - climatological method it was possible to achieve a certain model of occurrence of significant low level clouds during the presence of individual weather types. The results are applicable in aviation weather forecasting and it is possible to use them by characterizing of dynamic climate of other airports with similar orographic conditions.